Empathy, Autistic Tendencies, and Systemizing Tendencies—Relationships Between Standard Self-Report Measures - Sindermann, Cornelia; Cooper, Andrew; Montag, Christian (Frontiers in Psychiatry, 2019)
The aim of the present study was to investigate associations between four highly used self-report measures assessing empathy, measured as both a unidimensional and multidimensional construct, autistic tendencies and systemizing tendencies. Participants in this study completed the following self-report measures: The Interpersonal Reactivity Index (IRI) and the Empathy Quotient (EQ) to measure empathy, and the Autism Spectrum Quotient (AQ) and the Systemizing Quotient – Revised (SQ-R) to assess autistic and systemizing tendencies, respectively. The final sample consisted of N=1098 participants (304 males) without a diagnosed autism spectrum disorder, most of whom were university students. The IRI scale “Perspective Taking” and the EQ were negatively related to the AQ in male and female participants, while the IRI scale “Empathic Concern” was negatively related to the AQ in females only. Moreover, the AQ was positively related to the SQ-R in females only. Lastly, the SQ-R and a number of the empathy scales were significantly associated: For example, the EQ correlated positively with the SQ-R in both male and female participants. The results from this study illustrate how standard self-report measures of empathy, autistic and systemizing tendencies are associated with each other in a large sample not diagnosed with an autism spectrum disorder. Additionally, some potential gender specific effects are revealed.